Effects of onion (Allium cepa) dietary supplementation on turkey growth performance, internal organ weights and meat oxidative stability - Paredes, Manuel (2021)
The aim of this study was to determine the effect of different levels of nutritional supplementation of the onion bulb (Allium cepa) on the productive performance of the turkey, internal organ weight and oxidative stability of the meat. In total, 200 male Hybrid Converter turkeys from 42 to 98 days of age were assigned to four dietary treatments (five repetitions per treatment and 10 birds per repetition). All turkeys received the same concentrate feed, varying the levels of supplementation with chopped fresh onion (0, 1, 3 and 5% in relation to the weekly body weight). The fresh supplemented onion produced greater body weight gain, being the level of 1% sufficient to generate a better feed conversion index. The onion bulb did not improve carcass performance or heart, liver, spleen, gizzard, or abdominal fat weights; however, the best antioxidant capacity of fresh onion was found on turkey meat when stored at 4 °C for seven days.